The progress of organ protection mechanisms in sepsis - Zhu, Yuanjie; Cheng, Junjie; Sun, Zheyang; Jiang, Lu; Li, Min (Frontiers in Immunology, 2026)
BackgroundSepsis is a devastating condition with a high mortality rate, having garnered significant attention from physicians and scientists. Defined as life-threatening organ dysfunction resulting from a dysregulated host response to infection, sepsis poses a serious global health threat. Current treatment strategies for sepsis often remain inadequate and ineffective, increasing the burden on healthcare workers. Moreover, early detection of sepsis remains challenging, as existing scoring systems are ineffective in identifying and assessing pre-hospital sepsis. Therefore, early recognition and screening of sepsis symptoms are crucial for reducing the mortality rate and improving clinical outcomes.Main bodySepsis precipitates multi-organ dysfunction through mechanisms including dysregulated inflammation, immunosuppression, metabolic derangement, and endothelial injury. Multiple organ failure remains a leading cause of death in severe sepsis cases. Understanding how to improve the condition of sepsis is of great significance. Scientists and physicians have demonstrated that some organs possess intrinsic protective mechanisms against sepsis-induced damage, which is part of the disease tolerance mechanism.ConclusionThis review focuses on exploring organ protection mechanisms in sepsis, centered on four pivotal axes, inflammatory regulation, immune homeostasis, metabolic adaptation and endothelial integrity. While current research has begun to unravel these mechanisms, translating these findings into clinically effective therapies remains a promising challenge.